Pengaruh PENGARUH BIOINSEKTISIDA GRANULA CAMPURAN EKSTRAK BIJI SRIKAYA (Annonae squamosa) DAN DAUN SIRIH (Piper betle) TERHADAP MORFOLOGI TELUR Aedes aegypti - Firdha Novitasari; Dwi Wahyuni; Erma Sulistyaningsih (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Dengue hemorrhagic fever (DHF) is an important public health problem in Indonesia because its morbidity and mortality are quite high. Prevention by vector control methods with chemical insecticides adversely affects the environment. Research on granular bioinsectide mixture of betel leaf extract and sugar apple seeds against Aedes aegypti is expected to be used to break the chain of Aedes aegypti mosquitoes starting from the juvenile stage (eggs) as an effort to control the vector population naturally. Objective: This study aims to analyze the effect of granule bioinsecticide mixture of sugar apple seed extract and betel leaf on changes in the morphology of Aedes aegypti eggs. Methods: This study is a true-experimental study with a Post test Only Control Group Design design. The treatment group will be given a granular bioinsecticide, a mixture of sugar apple seed extract and betel leaf, positive control will be given abate while negative control will be given aquades. Each group uses 25 eggs with 3 repetitions. On day 3, all eggs will be observed using a stereo microscope to determine morphological changes. The data obtained will be analyzed using ordinal regression test. Results: the ordinal regression test got the value of ρ in the Wald test between (0.012 - 0.955)> α = 0.01. Conclusion: there is no effect of mixed granules of betel leaf and sugar apple seeds on the mortality of Aedes aegypti eggs. Further research is needed on new formulations using other natural ingredients to increase the effect of ovicides on Aedes aegypti.